MANAJEMEN PROGRAM PEMBELAJARAN MARKAS BAHASA ARAB DI PONDOK PESANTREN AL-KHOIROT MALANG - Rokim, Rokim; Muhlis, Nur Khozim; Fathih, Muhammad Amin (Idaarah: Jurnal Manajemen Pendidikan, 2023)
Organizing is one of the management functions that plays an important role in the realization of the planned learning program so that it can be maximized. Therefore, this research aims to examine the management of the Al-Khoirot Malang Islamic Boarding School Arabic Language Headquarters learning program. The research method used is descriptive qualitative. Data collection was carried out through observation, interviews and documentation. The data analysis technique is through data reduction, data decomposition and drawing conclusions. The research results show that learning program management at the Al-Khoirot Malang Islamic Boarding School Arabic Language Headquarters is implemented through several steps: (1) Determining learning objectives. The objectives are oriented towards four skills which include reading (qiro'ah), listening (istima'), writing (kitabah) and speaking (kalam); (2) Grouping of students is classified according to the level of ability of the students; (3) Vulnerable control is carried out by giving tasks and authority to asatidz at the Arabic language headquarters in accordance with their respective fields of expertise; and (4) The formation of the Arabic language headquarters structure is determined by the caregivers and supervisors of the Arabic language headquarters. The supervisor serves as the person who has the highest policy as well as the curriculum maker, giving authority to the Arabic Language Headquarters supervisor to form the divisions needed in the Arabic Language dormitory.